Studies of crime in Peru. A diachronic review of the production and concern of Academy - Huaytalla Quispe, Arturo (2017)
The work shows the different approaches of the studies of crime since the early twentieth century to the present in Peru. He argues that there has been an irregular interest in explaining the issue of crime, which were built different “objects” according to the concern of the time. So, initially it means the emergence of studies of crime, a second highlighting the lack of production, a third party that registers the emergence of critical studies, fourth time detailing production from studies of culture and identity and the latter scoring the widespread concern of crime with the low and uneven production of academia to understand the country’s main problem.